What does it drive the relationship between cardiovascular disease mortality and economic development? New evidence from Spain - Carla Blázquez-Fernández; David Cantarero-Prieto (Health Economics Review)
Abstract Background During the last decades, there has been a great interest on the link between macroeconomic conditions and health. More precisely, many studies had studied as health outcome cardiovascular disease mortality, focusing in different countries, determinants, and using numerous econometric techniques. Due to its importance, in this paper, we analyse cardiovascular disease mortality across the 17 Spanish regions over the period 2002–2019. Methods In doing so, we estimated several panel data models considering differences by sub-periods of time while also considering gender differences. That is, we transmit a difference on previous evidence by considering a longer period of time and different explanatory factors, so we provide new highlights for Spain. Results Our empirical results show that: (i) both socioeconomic and environmental factors have a significant importance; (ii) political factors appear not to be significant; and (iii) there exists a Mediterranean (macro-region) cardiovascular disease mortality pattern. Conclusions These results may have usefulness for cardiovascular disease mortality prevention in Spain.